Ethnicity, Immigration Status, And Driving Under The Influence Of Alcohol. Issue 4 (4th November 2022) - Le, Thao Lan; Tuck, Andrew; Agic, Branka; Ialomiteanu, Anca R.; McDonald, André J.; Mann, Robert E.; Wickens, Christine M.
Abstract: Background: Understanding risk factors for driving under the influence of alcohol (DUIA) informs development of effective interventions. This study examined the association between ethnicity, immigration status, and DUIA, exploring psychological distress and hazardous drinking as additional contributors. Method: Data were derived from the 2003-2011 cycles of the Centre for Addiction and Mental Health (CAMH) Monitor of 16, 101 adults from Ontario, Canada. Hierarchical binary logistic regression analysis assessed self-identified ethnicity and immigration status as predictors of DUIA, adjusting for sociodemographics and driving exposure (Model 1), psychological distress (Model 2), and hazardous drinking (Model 3). Results: In Model 1, respondents born outside of Canada had reduced odds of engaging in DUIA compared to those born in Canada (AOR = 0.72, 95%CI = 0.56 - 0.92). Relative to those identifying as Canadian, the odds of DUIA were significantly reduced for those identifying as East Asian (AOR = 0.28, 95%CI = 0.13 - 0.61) and South Asian (AOR = 0.52, 95%CI = 0.27 - 0.98). In Model 3, individuals who reported psychological distress (AOR = 1.69, 95%CI = 1.33 - 2.16) and those who reported hazardous drinking (AOR = 6.28, 95%CI= 5.13 - 7.69) were more likely to DUIA. Those identifying as East Asian continued to have reduced odds of DUIA compared to those identifying as Canadian (AOR = 0.38, 95%CI = 0.17 - 0.85). Conclusion: Individuals born outside of Canada were less likely to engage in DUIA than individuals born in Canada. Drivers who self-identified as East Asian were less likely to DUIA than those who self-identified as Canadian. Understanding ethnic differences underlying divergent risks for DUIA will improve prevention initiatives and remedial measures programming.